PEMBERDAYAAN MASYARAKAT GOHENG DAN SEKITARNYA DI MEUNASAH NAHDATUL FATAH DESA LAMTEUMEN TIMUR KECAMATAN JAYA BARU KOTA BANDA ACEH - Rosma Elly; Hajidin Hajidin.; Monawati Monawati. (Jurnal Pesona Dasar, 2019)
This article describes an empowerment activity conducted to train various alternative skills opportunities for Goheng community in order to try to increase their income so that they can improve their economy and their surroundings. In line with the objectives, the targets to be achieved is 20 housewives who can skillfully knit a total of 20 wallets and 60 brooches, 19 housewives and 1 male who can skillfully decorate with henna, 2 males and 18 housewives who are skilled in massage.